Prevention and treatment of neonatal hypothermia through an implementation science study in Jaltenango Chiapas, Mexico - Frade Garcia, Alejandro; Servitje Azcarraga, Lucila; Espinosa Olivas, María Azucena; García Ulloa, Laila Zulema; Garcia-Santisteban, Rodrigo; Hansen, Anne (International Society of Global Health, 2025)
Background Neonatal hypothermia is preventable but common, contributing to neonatal morbidity and mortality especially in low resource settings. Kangaroo Mother Care (KMC) is the preferred method to prevent hypothermia, but relying on it as a continuous heat source is challenging. This study introduced a novel Infant Warmer to complement KMC in a low resource community hospital through an implementation science approach. Methods We conducted a prospective, interventional cohort study in Jaltenango Chiapas, Mexico from January 2022 to November 2022. Our intervention was 1) an educational programme about the importance of euthermia and optimal thermoregulatory practices including KMC, and 2) provision of an Infant Warmer designed for low-resource settings with training of health care providers. Our hypothesis was that neonatal hypothermia rates would decrease after our intervention. Our aims were to reduce rates of hypothermia and increase knowledge and confidence regarding neonatal thermoregulation. The study had three phases: Pre-Intervention (January to May), Intervention, and Warmer Use (June to November). We collected clinical data during the Pre-Intervention and Warmer Use Phases, including temperature on admission and six hours later called ‘Follow-Up’. At three-time points we conducted surveys of health care providers regarding their knowledge of hypothermia, confidence in keeping babies warm, and attitudes regarding the Warmer. We also conducted a parent survey. Results We studied 372 newborns. Comparing Pre-Intervention to Warmer Use Phases, rates of hypothermia decreased from 62 to 27% on admission and 59 to 11% on Follow-Up. The mean admission and Follow-Up temperatures increased by 0.06°C (C) and 0.23°C (P=0.003) respectively. Healthcare providers’ knowledge of hypothermia and confidence in keeping newborns warm also improved throughout the study. Conclusions: We found high baseline rates of neonatal hypothermia in this low resourced hospital. We successfully lowered hypothermia rates by providing appropriate equipment to complement KMC and improved knowledge of hypothermia through education interventions. © The authors © International Society of Global Health.
Keywords: Neonatal hypothermia; Science study; Mexico